THE INFLUENCE OF TABANI POSTPARTUM DANGER SIGNS EDUCATION USING AUDIO VISUAL AND POSTER MEDIA ON INCREASING THE KNOWLEDGE OF POSTPARTUM MOTHERS AT THE PURBARATU HEALTH CENTER, TASIKMALAYA - Mustikasari, R. Fatimah Azahra; Megawati , Meti; Iriyanti, Bayu (UNIVERSITAS AIRLANGGA, 2026)
Background: Postpartum danger signs must be understood and known by mothers who have just given birth as a precautionary measure, as well as to obtain rapid treatment. The high maternal mortality rate (MMR) in Indonesia reaches 60% during the postpartum period, and around 50% of deaths in the postpartum period occur in the first 24 hours. Mothers with low levels of knowledge have a greater risk of experiencing health problems. The use of interesting educational media tools can accelerate changes in the mother's understanding, emotions and skills. Method: This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population consisted of all postpartum mothers residing in the working area of the Purbaratu Public Health Centre, Tasikmalaya City, during the period of May-June, totalling 42 individuals. The sampling technique used was non-probability sampling with a purposive sampling approach, resulting in a sample size of 42 respondents. The data were analysed using the Wilcoxon test. Result: Based on The results of the statistical analysis showed a significant increase in knowledge following the intervention. The mean pretest score was 20.26 ± 3.54, which increased to 24.98 ± 2.51 in the posttest, and this difference was statistically significant (ρ = 0.000). These findings indicate that providing TABANI (Postpartum Danger Signs) education through animated video and poster media effectively improved the knowledge of postpartum mothers in the Purbaratu Health Centre working area in 2025. Conclusion: This study demonstrates that providing educational information on TABANI (Postpartum Danger Signs) through audio-visual media and posters has proven effective in enhancing the knowledge of postpartum mothers. Therefore, TABANI (Postpartum Danger Signs) education can be used as a more efficient alternative in improving the knowledge of postpartum mothers.